PATH-ANALYSIS ON SEVERAL CHARACTERS IN POTENTIAL OF CORN PRODUCTION AND RESISTANCE TO DOWNY MILDEW - Pudjiwati, Eko Hary; Kuswanto, Kuswanto; Basuki, Nur; Sugiharto, Ariffin Noor (AGRIVITA, Journal of Agricultural Science, 2013)
This research was aimed at investigating both direct and indirect impacts, and heritability values of characters regarding the potential of corn production and resistance to downy mildew. The result of this investigation is required to determine some criteria taken into account for selection process of downy mildew-resistant corn breeding with high yield. The field experiment was conducted at Research Centre of Agriculture Faculty, Brawijaya University from January to April 2012. Five varieties of hybrid crown and five inbreeding lines were employed, and Randomised Block Design was applied with two replications. As observed, the characters held heritability ranging from average to high, except for heritability of length and width of stomata on the lower surface of the leaves which was categorised as low. Moreover, the stomata density found on lower surface of the leaves was directly and positively correlated to the intensity of attack by downy mildew, which, then, was used as criteria selection in downy mildew-resistance. The intensity of disease and the density of the stomata on lower surface of the leaves accounted for direct and negative correlation to corn production, while the length and diameter of corncob was responsible for direct and positive correlation to corn production. The betterment of corn production can be coped by improving the plant resistance to downy mildew and characters of corncob diameter.Keywords: path-analysis, corn, downy mildew Â